Evaluation of Local Organic Materials as Source of Organic Pesticides for Pest Control in Carrots. - Kanyesigye, Arozious (Kabale University, 2024)
A field experiment was carried out at the Faculty of Agriculture and Environmental Science Research farm at Kabale University located on Kikungiri Hill to evaluate the effect of local sources of organic pesticides for pest control in carrots during the 2023-2024 plating season. Five(5) treatments such as tobacco leaf extract, and wood ash extract, were applied at 10ll liters and a mixture of wood ash and tobacco leaf extract cypermethrin was applied at 30mls/15 liters, control were arranged in a randomized complete block design with 3 replicates Results showed a significant increase in p(<0.05) in growth, yield parameters, and effect on weed and pest population reduction under the use of different organic pesticides on pest control in carrots. The highest growth parameters were obtained under the use of a mixture of wood ash and tobacco leaf extract followed by tobacco leaf extract, wood ash extract, cypermethrin, and control respectively while the highest yield parameters were obtained under tobacco leaf extract followed by mixture, wood ash, cypermethrin, and control respectively The dominant weed was oxalis corniculate which dominated in the control treatment followed by cypermethrin, mixture, tobacco leaf extract, and wood ash extracts. Other weeds that were recorded include Tradescantia zebrina, amaranthas spinosus followed by Cyperus notodus, eymus repens, and Biden polilosa. The key pests recorded were black ants followed by Spiders, cutworms, and caterpillars respectively. Application of cypermethrin decreased Spiders by 66%,,36%, and 33% compared to wood ash extract, mixture, and control treatment respectively. The black ants population under control increased by 31%,5%,26%and 26% compared to tobacco leaf extract, a mixture of wood ash and tobacco leaf extract, and cypermethrin respectively. The highest value of carrot fruit weight was obtained under tobacco extracts followed by wood ash, the mixture of wood ash and tobacco leaf extract, cypermethrin, and control respectively leading to an increase in profit margins and benefit-cost ratio in these treatments respectively except under cypermethrin where the variable cost was higher than gross income. Generally the use of organic pesticides provided good results in controlling pests and reducing weed and yield.